TANGGUNG JAWAB NEGARA DALAM MELINDUNGI TENAGA KERJA INDONESIA (TKI) DI TAIWAN (KANTOR DAGANG DAN EKONOMI INDONESIA SEBAGAI SEBUAH KEDUTAAN BESAR DE FACTO DALAM KETIADAAN HUBUNGAN DIPLOMATIK) - Siti Safa’ati Rohmah (Jurnal Komunikasi Hukum, 2025)
The purpose of the research is to find out and analyze (1) Forms of abuse experienced by Indonesian Workers in Taiwan and the factors that contributing to their continued occurrence, and then (2) The role of the government in providing legal protection for Indonesian Workers in Taiwan through the Indonesian Economic and Trade Office. The type of research used is normative legal research using a statute approach, case study approach, and a conceptual approach. The legal materials used are primary, secondary, and tertiary legal materials. The technique of collecting legal materials used literature study technique and analyzed by descriptive technique. The results of the research show that (1) Indonesian Workers in Taiwan are vulnerable to abuse. The driving factor for the continued violation of Indonesian Workers Rights of the impact of the One China Policy which results in the absence of formal diplomatic relations and weakens their legal protection (2) The role of the Government in legal protection efforts for Indonesian Workers through IETO is to carry out consular functions properly. Actively provide assistance to Indonesian Workers who have problems, provide complaint services, providing legal aid and humanitarian assistance, administrative services such as document legalization, passport and visa extension. Although IETO is not a formal representative IETO always strives to protect the interests of all Indonesian citizens in Taiwan as best as possible.